Did the Japanese patient follow the doctor's orders? Mostly no! A public choice analysis of greenhouse gas emissions trading schemes in Japan before and after the earthquake - Sven Rudolph; Friedrich Schneider (Center for Economic Studies and ifo Institute (CESifo), 2011)
The Great Tôhoku-Earthquake and the following nuclear meltdown in Fukushima called the world's attention to Japans' energy and climate policy. Japan is one of the biggest emitters of greenhouses gases in the world and still far away from reaching its Kyoto target. Emissions trading systems have been used in Japanese climate policy since 2005. However, experiences have been disillusioning: Major emission reductions have not been achieved, and a function-ing market does not exist. Hence, we ask what the political reasons for the failure of carbon markets in Japan are and how they can be overcome. We use Public Choice arguments, but also analyze actual climate policy making in Japan on a case study basis. Thus, on the one hand, we identify the political obstacles of implementing ambitious greenhouse gas emissions trading systems in Japan, and, on the other hand, we evaluate Public Choice's arguments and environmental policy making.
Keywords: D62; D72; D73; Q48; Q54; Q58; 330; Japan; climate policy; emissions trading; Public Choice; case study